Prostate cancer incidence and agriculture practices in Georgia, 2000–2010. (September 2015) - Welton, Michael; Robb, Sara W.; Shen, Ye; Guillebeau, Paul; Vena, John
Abstract : Background: Georgia has prostate cancer incidence rates consistently above the national average. A notable portion of Georgia's economy is rooted in agricultural production, and agricultural practices have been associated with an increased risk of prostate cancer. Methods: Statistical analyses considered county age-adjusted prostate cancer incidence rates as the outcome of interest and three agricultural variables (farmland as percent of county land, dollars spent per county acre on agriculture chemicals, and dollars spent per county acre on commercial fertilizers) as exposures of interest. Multivariate linear regression models analyzed for each separately. Data were obtained from National Cancer Institute Surveillance, Epidemiology and End Results (SEER) 2000–2010, United States Department of Agriculture (USDA) 1987 Agriculture Survey, and 2010 US Census. Results: In counties with equal to or greater than Georgia counties' median percent African-American population (27%), dollars per acre spent on agriculture chemicals was significantly associated ( P = 0.04) and dollars spent of commercial fertilizers was moderately associated ( P = 0.07) with elevated prostate cancer incidence rates. There was no association between percent of county farmland and prostate cancer rates. Conclusion: This study identified associations between prostate cancer incidence rates, agriculture chemical expenditure, and commercial fertilizer expenditure in Georgia counties with a population comprised of more than 27% of African Americans.